2018
DOI: 10.1155/2018/8046541
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of 68Ga-PSMA-11 with a Synthesis Module for Micro PET-CT Imaging of PSMA Expression during Prostate Cancer Progression

Abstract: Objective To synthesize 68Ga-Glu-urea-Lys(Ahx)-HBED-CC (68Ga-PSMA-11) with a synthesis module and investigate PET-CT imaging to monitor PSMA expression during prostate cancer (PCa) progression and tumor growth in mice bearing subcutaneous PCa xenografts. Method The radiochemical purity and stability of  68Ga-PSMA-11 were determined via radio-HPLC. The PCa cell lines of different PSMA expression levels (PC3, VCAP±, CWR22RV1+, and LNCaP++) were selected to mimic the PCa progression. 68Ga-PSMA-11 biodistribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…As expected and already reported using PSMA-based radioligands in PCa models, the tumour uptake of [ 68 Ga]Ga-PSMA-11 was high in 22Rv1 derived tumour and negative in PC3 one, well correlated with PSMA expression [29]. Similarly to Wang et al [29], we found elevated uptake and undesired retention of [ 68 Ga]Ga-PSMA-11 in kidneys, in good agreement with the substantial PSMA expression observed in this organ in mice and in humans [30]. Despite [ 68 Ga]Ga-PSMA-11 PET/CT being currently widely used in patients for the management of all stages of PCa, potential pitfalls therefore still exist in PSMA-based imaging approaches, especially due to the lack of PSMA overexpression in some primary tumours as well as the loss of PSMA expression in poorly differentiated tumour with NED [10,31].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As expected and already reported using PSMA-based radioligands in PCa models, the tumour uptake of [ 68 Ga]Ga-PSMA-11 was high in 22Rv1 derived tumour and negative in PC3 one, well correlated with PSMA expression [29]. Similarly to Wang et al [29], we found elevated uptake and undesired retention of [ 68 Ga]Ga-PSMA-11 in kidneys, in good agreement with the substantial PSMA expression observed in this organ in mice and in humans [30]. Despite [ 68 Ga]Ga-PSMA-11 PET/CT being currently widely used in patients for the management of all stages of PCa, potential pitfalls therefore still exist in PSMA-based imaging approaches, especially due to the lack of PSMA overexpression in some primary tumours as well as the loss of PSMA expression in poorly differentiated tumour with NED [10,31].…”
Section: Discussionsupporting
confidence: 87%
“…PSMA has obviously emerged in the past decade as one of the most favourable targets for PET imaging and radionuclide based therapy [28]. As expected and already reported using PSMA-based radioligands in PCa models, the tumour uptake of [ 68 Ga]Ga-PSMA-11 was high in 22Rv1 derived tumour and negative in PC3 one, well correlated with PSMA expression [29]. Similarly to Wang et al [29], we found elevated uptake and undesired retention of [ 68 Ga]Ga-PSMA-11 in kidneys, in good agreement with the substantial PSMA expression observed in this organ in mice and in humans [30].…”
Section: Discussionsupporting
confidence: 71%
“…(10.3 ± 2.2 nM in C4-2 cells) 10 and for 68 Ga-PSMA-11 by Wang et al . (4.3 ± 0.8 nM in LNCaP cells) 19 and Sanchez-Crespo et al . (27.05 nM in LNCaP cells) 20 .…”
Section: Discussionmentioning
confidence: 86%
“…In vitro characterization of 18 19 and Sanchez-Crespo et al (27.05 nM in LNCaP cells) 20 . The recently evaluated 18 F-PSMA-BCH demonstrated a comparable K d value of 2.90 ± 0.83 nM in 22Rv1 cells 21 .…”
Section: Discussionmentioning
confidence: 97%
“…Protocols for the manual, semiautomatic and fully automatic production of [ 68 Ga]Ga‐PSMA‐11 have been published with overall radiochemical production yields for manual and semiautomatic processes generally >90% 17–22 and fully automated procedures including product formulation ranging between 57‐80% decay‐corrected (d.c.) radiochemical yield 23–28 . Manual and fully automated production of [ 177 Lu]Lu‐PSMA‐617 has been reported in >90% radiochemical yields 29–32 …”
Section: Introductionmentioning
confidence: 99%